2023
DOI: 10.1002/ijc.34640
|View full text |Cite
|
Sign up to set email alerts
|

(Pre)treatment risk factors for late fatigue and fatigue trajectories following radiotherapy for breast cancer

Abstract: Fatigue is common in breast‐cancer survivors. Our study assessed fatigue longitudinally in breast cancer patients receiving adjuvant radiotherapy (RT) and aimed to identify risk factors associated with long‐term fatigue and underlying fatigue trajectories. Fatigue was measured in a prospective multicenter cohort (REQUITE) using the Multidimensional Fatigue Inventory (MFI‐20) and analyzed using mixed models. Multivariable logistic models identified factors associated with fatigue dimensions at 2 years post‐RT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Three studies investigating fatigue trajectories indicated that having constantly high fatigue was associated with depression/ anxiety. [21][22][23] Thus, it appears reasonable that future studies examine this subgroup and investigate if the efficacy of fatigue treatment differs between cancer survivors with and without depression/anxiety. It would be of relevance for patients suffering from fatigue along with depressive symptoms if, for example, exercise or a psychological intervention would be more beneficial for them.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies investigating fatigue trajectories indicated that having constantly high fatigue was associated with depression/ anxiety. [21][22][23] Thus, it appears reasonable that future studies examine this subgroup and investigate if the efficacy of fatigue treatment differs between cancer survivors with and without depression/anxiety. It would be of relevance for patients suffering from fatigue along with depressive symptoms if, for example, exercise or a psychological intervention would be more beneficial for them.…”
Section: Discussionmentioning
confidence: 99%